Pendistribusian Dana Zakat Untuk Pelayanan Kesehatan Pada LAZ Ibbadurrahman Kota Duri - Uli Usandari (ZAWA: Management of Zakat and Waqf Journal, 2023)
The main problem in this thesis is the distribution of zakat funds with the problem ofwhat are the procedures for health services at LAZ Ibbadurrahman Duri City and what are the obstacles encountered in distributing zakat funds for health services at LAZ Ibbadurrahman Duri City. The purpose of this discussion is to identify and explain the procedures for distributing zakat funds for health services at LAZ Ibbadurrahman Duri City and the obstacles encountered in distributing zakat funds for health services at LAZ Ibbadurrahman Duri City. The type of research that the authors use is a type of field research (Field Research), namely obtaining data for the problems studied. The data collection technique that the writer uses is through interviews and documentation. Data analysis techniques in the following ways: data reduction, data presentation, and drawing conclusions. From the research conducted by the authors in the field, it can be concluded ┬áthat ┬áthe ┬áprocedure ┬áfor ┬ádistributing ┬ázakat ┬áfunds ┬áfor health ┬áservices┬á┬á ┬áat┬á┬á┬á ┬áLAZ┬á┬á┬á ┬áIbbadurrahman┬á┬á ┬áCity┬á┬á ┬áof┬á┬á┬á ┬áDuri,┬á┬á┬á┬á namely:┬á┬á┬á ┬áLAZ Ibbadurrahman introduced its program on health to the dhuafa community as well as with ┬áconditions, ┬áthe ┬ádhuafa ┬ábrought┬á┬á LAZ┬á ┬áIbbadurrahman/LAZ ┬áIbbadurrahman Primary Clinic to bring condition. While the obstacle is the limited funds that cannot finance all the needs of the community because it is┬á┬á┬á ┬ástill┬á┬á┬á┬á lacking,┬á┬á┬á ┬áthere┬á┬á┬á ┬áis insufficient┬á┬á ┬áinfrastructure┬á┬á ┬áat┬á┬á┬á the┬á┬á ┬áLAZ Ibbadurrahman Primary Clinic, so LAZ Ibbadurrahman refers patients to Pekanbaru-Dumai.